2009
DOI: 10.1136/oem.2008.039578
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma and allergy in snow crab processing in Newfoundland and Labrador

Abstract: The prevalences of OA and OAl are high in snow crab-processing workers of Canada's East Coast. Cumulative exposure to snow crab allergens was related to the prevalences of OA and OAl in a dose-response manner taking into account atopy, gender and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 26 publications
7
53
1
5
Order By: Relevance
“…We did not have adequate research funds to measure specific IgE antibodies in this study. Previous studies have found that immunological sensitization to snow crab allergens was significantly associated with asthma among snow crab processing workers (8,10,34). Although this study was unable to estimate immunological sensitization to snow crab allergens, it can be said that this type of sensitization may be significantly associated with asthma among Japanese snow crab processing workers.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have adequate research funds to measure specific IgE antibodies in this study. Previous studies have found that immunological sensitization to snow crab allergens was significantly associated with asthma among snow crab processing workers (8,10,34). Although this study was unable to estimate immunological sensitization to snow crab allergens, it can be said that this type of sensitization may be significantly associated with asthma among Japanese snow crab processing workers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report a high incident of occupational asthma in workers processing snow crab (Chionoecetes opilio) and king crab (Paralithodes camtschaticus), but other symptoms as rhinitis, conjunctivitis, and skin rash are also registered (Orford and Wilson, 1985;Cartier et al, 1986;Ortega et al, 2001;Howse et al, 2006;Gautrin et al, 2009). Although a majority of the literature point to an IgE-mediated mechanism for the development of respiratory disease among crab processing workers, there are reports that fail to show a clear correlation between crab specific IgE and new incidents of asthma-like and bronchitis cases (Ortega et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Adverse health effects from bioaerosol exposure (Eduard et al 2012;Shiryaeva et al 2013;Watanabe et al 2016;Gautrin et al 2010;Jeebhay et al 2008) such as immunological sensitisation, respiratory symptoms, bronchial hyper-responsiveness and occupational asthma have been found in exposed seafood workers. Sensitisation is documented in workers processing fish, mussels, prawns and crabs.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse health effects or a dose-response relationship between levels of different components of bioaerosols and respiratory symptoms, allergy, and asthma are found in seafood workers, including snow crab workers (Lopata and Jeebhay 2013;Jeebhay 2011;Jeebhay et al 2001;Gautrin et al 2010). …”
Section: Introductionmentioning
confidence: 99%